2n+4−2(2n)2(2n+3)when simplified is = ?2n+4−2(2n)2(2n+3)when simplified is = ?\eqalign{ & \frac{{{2^{n + 4}} - 2\left( {{2^n}} \right)}}{{2\left( {{2^{n + 3}}} \right)}} \cr & {\text{when simplified is = ?}} \cr} " /> 2n+4−2(2n)2(2n+3)when simplified is = ?2n+4−2(2n)2(2n+3)when simplified is = ?\eqalign{ & \frac{{{2^{n + 4}} - 2\left( {{2^n}} \right)}}{{2\left( {{2^{n + 3}}} \right)}} \cr & {\text{when simplified is = ?}} \cr} " /> 2n+4−2(2n)2(2n+3)when simplified is = ?2n+4−2(2n)2(2n+3)when simplified is = ?\eqalign{ & \frac{{{2^{n + 4}} - 2\left( {{2^n}} \right)}}{{2\left( {{2^{n + 3}}} \right)}} \cr & {\text{when simplified is = ?}} \cr} " />
Post your Comments